The Evaluation of Dengue Surveillance System Depok City, 2023 - Khairiah; Helda; Hidayat Nuh Ghazali (Gema Lingkungan Kesehatan, 2025)
Dengue remains a global and national public health issue. In Depok City, the incidence rate (IR) is 53.53 per 100,000 population, higher than West Java’s IR of 38 and the national target of 10 per 100,000. This study uses a descriptive method that assesses structure, core functions, supporting functions, and system attributes to evaluate the dengue surveillance system based on its attributes. Primary data were collected through interviews with the Depok City Health Office, five public health offices, two hospitals, two clinics, two independent midwives, and one private laboratory. Secondary data were obtained from dengue report documents. The study examines surveillance structure, legal components, coordination, and strategies, which remain suboptimal. Core functions, including case detection, recording, confirmation, and reporting, are optimal, but data analysis, interpretation, and information dissemination are lacking. A feedback reporting mechanism is absent. Supporting functions like guidelines, supervision, monitoring, and evaluation are in place, but resource limitations persist. Surveillance attributes such as simplicity, completeness, timeliness, and flexibility are optimal. However, reporting representation remains incomplete despite good reporting acceptance, and its usefulness is not maximised. Overall, dengue surveillance has yet to fully achieve its goal of monitoring disease trends and enabling early outbreak detection. Resource and capacity constraints hinder effectiveness. Strengthening surveillance officers and healthcare providers, improving coordination, allocating funds, and implementing regular monitoring, evaluation, and weekly feedback bulletins are essential steps.